Paraganglioma Presenting as Postpartum Fever of Unknown Origin - Shraddha Narechania; Amrita Bath; Laleh Ghassemi; Chetan Lokhande; Abdo Haddad; Ali Mir Yousuf; Jessica Marquard; K. V. Gopalakrishna (Case Reports in Endocrinology)
A young healthy postpartum mother presented with intermittent high fevers and tachycardia. Appropriate testing was done to rule out infectious causes including pan cultures but no identifiable infectious source was found. A CT of the abdomen showed a retroperitoneal mass with two small pulmonary nodules and a bony metastatic lesion. She was found to have stage 4 extra-adrenal paraganglioma with metastases to the lungs and spine. She underwent resection of the mass and is currently undergoing palliative radiation to the spine for pain control. Subsequent genetic testing identified a likely pathogenic variant in SDHB, confirming a diagnosis of Hereditary Paraganglioma-Pheochromocytoma syndrome.